ANALISIS HUKUM ATAS PENGGUNAAN TANDA TANGAN ELEKTRONIK RELEVANSI DENGAN PERLINDUNGAN HUKUM TERHADAP NOTARIS DAN SUBSCRIBER - DEVINA DEVINA (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1. Prof. Dr. Saidin, SH, MHum2. Notaris Dr. Suprayitno, SH, MKn3. Notaris Dr. Tony, SH, MKn  Rapid development of information technology influences legal profession such as notarial profession, especially in the concept of cyber-notary in which a Notary has the authority to certify electronic transaction, using electronic signature. However, a subscriber's electronic signature is very vulnerable to be misused so that he needs legal protection. The objective of the research was to find out legal status of using an electronic signature in notarial position in electronic transaction and legal protection for a Notary and a subscriber. The research used juridicial normative method which was referred to library research and other secondary data which were related to the subject matter of the research. It is found that electronic signatures have not been applied in using Notarial deed since it is not recognized in the legal provisions concerning electronic signature in making electronic Notarial deed. This is because a Notarial deed which is signed electronically does not have any legal force as evidence since it is considered as an underhanded certificate. So far, there has not been legal provision concerning the use of electronic signature in an authentic deed. Rapid development information technology has the effect on personal data which is vulnerable to the misuse when it is not legally protected. In practice, Notaries do not use electronic signatures in their deeds since there is no regulation which regulates the use of electronic signatures so that they do not have legal ground to do their authority since they are not protected by law. Keywords: Cyber Notary, Electronic Signature, Notary, Personal Data